MERUMUSKAN FAKTOR PENYEBAB DAN SOLUSI PELECEHAN SEKSUAL MENGGUNAKAN PERSPEKTIF PSIKOLOGI, SOSIAL, DAN AGAMA - Ahmad Saifuddin (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Life problems include many things, one of which is sexual harassment. The data shows that the number of sexual harassment is increasing. In addition, sexual harassment can occur at any time and in various contexts. However, there is still little research related to sexual harassment that involves various perspectives. The multi-perspective research is important so that the solution to handling sexual harassment is comprehensive. The study was conducted by systematic review. The results showed that the study of sexual harassment using psychological, social, and religious perspectives would produce more comprehensive alternative solutions. For example, increasing knowledge about sexual harassment, improving the construction of women's image and position between men and women, self-control, increasing assertive behavior, providing support to victims of sexual harassment, to increasing religiosity.Keywords: psychology; religion; sexual harassment; social